2014
DOI: 10.1021/es5016839
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of Selected Brominated Flame Retardants in Nursing Women: Implications for Human Exposure

Abstract: We have examined several emerging brominated flame retardants (BFRs) including 2-ethyl-1-hexyl-2,3,4,5-tetrabromobenzoate (TBB), bis(2-ethylhexyl) tetrabromophthalate (TBPH), 1,2-bis(2,4,6-tribromophenoxy) ethane (BTBPE), 4,5,6,7-tetrabromo-1,1,3-trimethyl-3-(2,3,4,5-tetrabromophenyl)-indane (OBIND), and decabromodiphenyl ethane (DBDPE) in paired human maternal serum (n = 102) and breast milk (n = 105) collected in 2008–2009 in the Sherbrooke region in Canada. Three legacy BFRs were also included in the study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(68 citation statements)
references
References 46 publications
6
62
0
Order By: Relevance
“…Lesser blood to milk partitioning of BEH-TEBP, which has a higher molecular weight and higher estimated logK OW compared with EH-TBB (706.14 Da and 11.95 compared to 549.92 Da and 7.73), could account for lower observed levels of BEH-TEBP tissue accumulation resulting from lactational transfer (U.S. Environmental Protection Agency, 2012). Similarly, Zhou et al (2014) observed lesser serum to breast milk partitioning of BEH-TEBP compared with EH-TBB in humans. BEH-TEBP was only detected in serum above MDL levels in dams at the high dose, also supporting a low absorption potential (Fig.…”
Section: Beh-tebpmentioning
confidence: 81%
“…Lesser blood to milk partitioning of BEH-TEBP, which has a higher molecular weight and higher estimated logK OW compared with EH-TBB (706.14 Da and 11.95 compared to 549.92 Da and 7.73), could account for lower observed levels of BEH-TEBP tissue accumulation resulting from lactational transfer (U.S. Environmental Protection Agency, 2012). Similarly, Zhou et al (2014) observed lesser serum to breast milk partitioning of BEH-TEBP compared with EH-TBB in humans. BEH-TEBP was only detected in serum above MDL levels in dams at the high dose, also supporting a low absorption potential (Fig.…”
Section: Beh-tebpmentioning
confidence: 81%
“…The only previous study utilizing GC-MS-MS for the determination of PBB exposure was a recent investigation of emerging and legacy BFRs in paired maternal breast milk and serum (30). In this study, determination of two PBB congeners, PBB-153, PBB-209, and six additional BFR compounds was performed using electron-capture negative chemical ionization mode with peak identification and quantification by selected ion monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…LOD for PBB-209 was derived from the lowest standard concentration that produced S/N ratio ≥3, and was reported as 0.49 ng/g. Paired sample duplicates (n = 18) were reported to have a mean percent difference of 13% for PBB-153 (30). Each of these existing methods fails to address both of the previously identified major limitations in exposure characterization for epidemiologic research on PBB exposure, improvement in LOD and unequivocal determination of multiple congeners.…”
Section: Discussionmentioning
confidence: 99%
“…In Guangzhou, one of the largest industrial cities in China, the median concentration of DBDPE in hair samples was found be 17.8 ng/g lipid (Zheng et al 2011). In contrast, DBDPE was not detected in human tissue in Canada, New Zealand, and the USA (Mannetje et al 2013;Petreas et al 2012;Zhou et al 2014). The levels observed in some samples in this cohort should be not surprising given that Dhaka is the industrial epicenter of Bangladesh, where it is likely that DBDPE is currently being used as a replacement for decabromodiphenyl ether and octabromodiphenyl ether mixtures-BFRs that are facing increasing regulation and are starting to be phased out of the commercial market due to concerns for environmental and human health (Luo et al 2010).…”
Section: Discussionmentioning
confidence: 98%